(untitled) (Journal of the College of Basic Education, 2022)
The study area is located within the sedimentary plain area with an area of (8153 km2), and the climate of the study area is characterized by drought, and this was shown by collecting climatic elements, describing and analyzing them for monitoring stations in the study area, which greatly affected the emergence and development of the studied phenomenon (sand dunes), and it was found through The study is the spread of several types of sand dunes, represented by crescent, longitudinal and transverse dunes, nets and sand waves, which were distributed differently in the study area as it shows the clear effect of sand dunes on human activities represented in agricultural lands, transportation methods, and archaeological and tourist places, and this is consistent with the increase in wind movement, which in turn leads to Increasing the sandy flow, which doubles the negative effects on human activity. Therefore, it is necessary to find the most appropriate ways to stabilize these dunes in an attempt to avoid or at least reduce the severity of the problems resulting from sand movement